Advanced mechanics of composite materials and structural elements - Vasiliev, Valery V.; Morozov, Evgeny V. (Burlington : Elsevier Science, 2013)
Advanced Mechanics of Composite Materials and Structural Elements analyzes contemporary theoretical models at the micro- and macro levels of material structure. Its coverage of practical methods and approaches, experimental results, and optimization of composite material properties and structural component performance can be put to practical use by researchers and engineers. The third edition of the book consists of twelve chapters progressively covering all structural levels of composite materials from their constituents through elementary plies and layers to laminates and la.
Includes bibliographical references.
Keywords: Composite materials -- Mechanical properties